Assessing Theoretical Frameworks, Human Resources Management Implications and Emerging Technologies on the Water, Energy and Food (WEF) Nexus - Love David; Omoseni Adepoju (Journal of Digital Food, Energy & Water Systems)
The interactions of water, energy, and food resources resulting in WEF nexus thinking have been conceptualized as an integrated framework to achieve the security of the three vital resources. However, there are some gaps in WEF nexus research, which constrains the understanding and actualization of the nexus. Hence, this review paper aims to assess theories, human resource management implications, and emerging technologies' effect in understanding the nexus for its actualization. The research employed a qualitative research methodology to achieve the research objectives. The research findings revealed six (6) significant theories that can aid the understanding and actualization of the WEF nexus. The research also revealed that human resource management is strategic, highlighting the need for nexus thinking among human resources. Furthermore, the study revealed the three major emerging technologies of Artificial Intelligence, Big data analytics, and Internet of Things (IoT), which are shaping the WEF nexus through innovations and shaping the nature of the nexus. The study concluded that there is an interaction between the theories and human resources management for attaining the WEF nexus, which affects the extent of the sustainability of the innovations introduced by the emerging technologies. The study recommended quantification of the theories, training on nexus thinking of the current human resource in the WEF sectors, and capital investment on emerging technologies in the WEF nexus.